Effects of Auditory Working Memory Tasks while Switching between Autonomous and Manual Driving. (September 2016) - McCarty, Madeleine; Funkhouser, Kelly; Zadra, Jonathan; Drews, Frank
As the prevalence of autonomous vehicles onto the road increases, understanding the cognitive processes of the inevitably distracted driver is important. When engaged in a secondary task while driving, the driver's limited supply of attentional resources is diminished, resulting in less attention available to process the unpredictable road ahead. While driving distracted causes performance to suffer across the board (Fitousi & Wenger, 2011), some individuals are more apt at multitasking than others due to a high working memory capacity (WMC). We evaluated the differences in braking reaction times (RT) according to individual difference in WMC, specifically while driving in an autonomous car simulation and engaged in a cognitively demanding task. Results showed an interaction between current level of cognitive load and an individual's WMC where individuals who scored lower on a complex operation span task (OSPAN) experienced greater RTs compared to individuals who scored higher. Average RT during the autonomous scenario, in which OSPAN was concurrently performed, yielded a 33% increase in RT compared to baseline RT with the same OSPAN task. Additionally, sleep and length of time spent in autonomous mode influenced RT.